Laser Hardening of the Functional Surfaces of Machine Tools - Šramhauser, Karel; Kuśmierczak, Sylvia (Manufacturing Technology Journal, 2016)
The purpose of using modern technology is to reduce costs, facilitate the work and simplify as far as the most comprehensive set of operations. One of many modern technological processes involved in the refining of materials are technologies of surface hardening using a laser beam. This method can harden precisely defined areas with minimal thermal influence of surrounding areas it is possible to achieve less residual stress and less distortion of components compared the volumetric hardening, it is also possible to use controlled robotic units and all for the absence of cooling, which proceeds spontaneously to the surrounding material itself and atmosphere. These advantages of laser surface hardening are used by companies for which the prospect of minor damage to the material, increase of the material durability, material stiffness ensuring etc. is initiation for the use of modern technology.
Keywords: laser hardening; cast iron; hardness; microstructure